A systematic investigation into a novel method for preparing carbon fibre–carbon nanotube hybrid structures. (November 2016) - Li, Quanxiang; Church, Jeffrey S.; Naebe, Minoo; Fox, Bronwyn L.
Abstract: By electrospraying solvent dispersed carbon nanotubes (CNTs) with a binder onto carbon fibre (CF), hybrid structures, with an end aim to improve interfacial bonding in composites, were formed. The electrospray parameters controlling the modification of the CNT morphologies were studied. High-speed camera observations found applied voltage was critical for determining spray mode development. Electric field simulations revealed a concentrated electric field region around each fibre. Both voltage and distance played an important role in determining the CNT morphology by mediating anchoring strength and electric field force. The forming mechanism investigation of different surface morphologies suggested that binder with appropriate wetness gives freedom to the CNTs, allowing them to orientate radially from the CF surface. Linear density (LD) measurements and thermogravimetric analysis revealed that a 10 min coating increased the LD of a single CF filament by up to 31.7% while a 1 h treatment increased fibre bundle mass by 1%.